Book Review for Denis O’Hara Hope in Counselling and Psychotherapy - Jenny Coburn (Psychotherapy and Counselling Journal of Australia)
Associate Professor Denis O’Hara’s first book examines the role of hope in healing and personal growth, and argues that hope takes a central position both in life, and in the process of therapeutic change. He notes that despite hope being recognised as one of the "common factors in therapeutic change, and despite its frequent presence in our daily lives, it remains an elusive concept. The American 19th century poet Emily Dickinson wrote that hope is "the thing with feathers that perches in our soul." (1890/1999, p. 19 my italics). In many ways, hope remains at the periphery of our conscious awareness, defying a concrete definition. This is a point that is embraced by this book. As noted in the preface, "Hope is everywhere yet hardly visible" (O’Hara, 2013, p. ix). One of the aims of this book is to bring hope out of the shadows and make it more visible and available to those of us who work with people therapeutically.